Neanderthal teeth from moula‐guercy, Ardèche, France. Issue 3 (4th June 2013) - Hlusko, Leslea J.; Carlson, Joshua P.; Guatelli‐Steinberg, Debbie; Krueger, Kristin L.; Mersey, Ben; Ungar, Peter S.; Defleur, Alban
ABSTRACT Here we describe dental remains from a Neanderthal fossil assemblage from Moula‐Guercy, France. Our report demonstrates that the Moula‐Guercy hominid remains contribute important morphological, developmental, and behavioral data to understanding Neanderthal evolutionary history. We include gross comparative morphological descriptions and enamel surface microstructure and microwear data. These teeth reveal numerous characteristics that are diagnostic of Neanderthals and provide no evidence for the presence of any other hominid taxa. Enamel growth increment data from the Moula‐Guercy specimens yield evidence of a Neanderthal pattern of development, although at the lower end of the range of variation. The presence of a significant number of linear enamel hypoplasias indicates that these individuals were stressed during childhood. Molar microwear data suggest that these Neanderthals did not differ significantly from modern humans in terms of the fracture properties of the food they were consuming. The incisor microwear and macro striations provide evidence that these individuals may have been using their anterior teeth as tools, similar to the practices of several modern human populations such as the Inuit, Ipiutak, and Australian Aboriginals, and reminiscent of evidence from other Neanderthals from Krapina, Croatia, as well as the 600, 000 year old hominids from Sima de los Huesos, Spain. Am J Phys Anthropol 151:477–491, 2013.© 2013 Wiley Periodicals, Inc.